Society, politics, and economic development some exploratory notes - Ferrer, Ricardo D. (1984)
This paper attempts to undertake a further discussion of the dynamics of social, political, and economic development. The author believes that there exist broad but well-specified theories of social, political, and economic development, one of which is Marxism which permits formulation of broad but empirically testable hypotheses. The paper presents some empirical hypotheses deducible from the Marxist theory of social change, which are subsequently tested using the same set of data used by Adelman and Morris (1967). Basically, the results demonstrates that the Marxist proposition about social change can be subjected to standard empirical tests, and provide empirical support to two fundamental Marxist propositions, namely that the rate of social and economic development increases upon attaining some thresholds in the development of capitalist forces in society and that imperialism, specified in some manner, is a significant factor in economic development.
Keywords: Economic development; Social change; Economics -- Research